Death In Victorian Toronto, 1850-1899 - Barkin, Risa; Gentles, Ian (Urban History Review / Revue d'histoire urbaine, 1990)
A study of the 24,124 deaths recorded in the burial registers of the Putter's Field Cemetery and the Necropolis from 1850 to 1899, indicates that Toronto, like other nineteenth-century cities, experienced very high mortality. The average age at death rose gradually over the fifty-year period, but infants under the age of one year constituted over 40 percent of all burials. Tuberculosis was the leading cause of death among adults, while poor water produced substantial mortality from typhoid.